Exploring Pattern of Smartphone Addiction among Students in Secondary Schools in Lagos State and its Counselling - Onyeka, EJIE Benedette; Chisom, EJIE Oscar; Nchedochukwu, EJIE Cynthia; Uchechukwu, EJIE Ann; Ikechukwu, EJIE Brian (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: RSmartphone addiction could be described as smartphone over-dependence or smartphone overuse. It is a form of addiction that has become one of the most prevalent non-drug addictions today. Smartphone overuse was nevertheless shown to imply various types of dysfunctional behaviours and adverse consequences.This paper therefore, eexplored pattern of smartphone addiction among students in secondary schools in Lagos state and its counselling. One research question and onehypothesis were raised to guide the research. The sample consisted of one hundred and fifty (150) students randomly selected from students in secondary schools in Lagos state. A 30-item questionnaire titled “Pattern of Smartphone Addiction” (PSA) was designed for data collection. Cronbach’s Alpha reliability coefficient of the instrument stood at 0.84. The study adopted the descriptive survey design to seek information. Data analysis was carried out with the use of percentages and Multiple Regression Analysis to test the hypotheses at 0.05 level of significance. Results showed that music / movies, virtualrelationship, cybersex and videogames are found to have statistically significant positive correlation to smartphone addiction and they are the strongestpattern of smartphone addiction among students in secondary schools in Lagos state.. Counsellors, parents and teacher should watch out for these pattern of smartphone addiction and properly guide the students.ef